Unraveling complexity of celebrity worship and its associations with mental health among emerging adults in China - Dannuo Wei; Yu-Te Huang (Humanities & Social Sciences Communications)
Abstract The digital media and the celebrity-making industry have drastically fueled celebrity worship, an evolving and complex human behavior. However, existing studies seem to oversimplify celebrity worship as a continuum ranging from normal to pathological. This study addresses this gap by developing a framework to classify distinct fan types and validate them with empirical data. A nationwide online survey was conducted with 806 Chinese emerging adults who acknowledged having a favorite celebrity. Six fan profiles were identified through Latent Profile Analysis. We then compared our classification with the widely used Celebrity Attitude Scale (CAS) to predict mental health outcomes among all participants and by gender. Results revealed significant differences across fan types on anxiety and the psychological well-being sub-dimension. The CAS score was not significantly associated with anxiety or depressive symptoms. Associations between fan types and mental health outcomes varied by gender. These findings highlight the complex nature of celebrity worship.